Penyalahgunaan Narkotika pada Kalangan Anak di Bawah Umur Ditinjau dari Sosiologi Hukum - Khalaf, Muhammad Baharuddin; Senjaya, Oci (Peneliti.net, 2023)
This research aims to find out the efforts to combat narcotics by minors, as well as find out the factors that influence underage children to commit narcotic narcotics crimes. This research was conducted at BNN Karawang regency. The type of legal research used by researchers is a type of empirical legal research with a sociological legal approach. Empirical legal research is a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. Data collection in the Library study was carried out by research by studying and collecting data obtained from books, the internet, pre-statutory regulations and other documents, this analysis was then presented in a descriptive form. The results of the study show that efforts to deal with narcotics by children in the district have been running but have not been optimal, so that the expected results have not been realized.